(untitled) - Duffy, James E. (Tinley Park, Illinois, 1997)
The book consists of six sections. Section One reviews fundamentals for those with no previous training in automotive technology. Section Two details engine construction and operation. Section Three summarizes the theory and service of engine-related systems (starting systems, ignition systems, fuel systems, diesel injection systems, turbochargers,...). Section Four explains how to diagnose both mechanical and performance problems. It also summarizes engine tune-up procedures. Section Five covers the overhauling or rebuilding of engines. And section Six summarizes ASE certification tests and career success
Keywords: Xe ô tô,Automobiles,Motors